Speak now : Taylor's version [compact disc] - Swift, Taylor, 1989-; Swift, Taylor, 1989- (Republic Records, 2023)
"Speak Now" includes re-recorded versions of 16 songs from the deluxe edition of Taylor's third studio album and six previously unreleased "From the Vault" songs.